Effect of the of poultry manure addition and foliar applicatio of 4TOP fertilizer on some physical and chemical properties of soil , growth and yield of millet. - Habeeb, Hamied Ajeel (Journal of Kerbala for Agricultural Sciences, 2014)
This experiment was conducted in the tissue culture laboratory, Horticulture Department, Agriculture College, University of Baghdad, to investigate the influences of abscsic acid (ABA) and the physical status of growing media for two potato cultivars on the production and qualitative characters of microtubers. Different ABA concentration of 0.0 , 50 , 100 , 150 and 200 mg .l-1 was added to the two growing media the first one was liquid ( without agar ) while the other type the semi-solid media ( 7g.l-1 agar ) for two potato cultivars , Desiree and Revira . Adding ABA at the rate of 0.5 mg . l-1 significantly increased the number, weight , diameter of the microtubers in addition the reducing sugar content and the percentage of protein , while adding 0.25 mg.l-1ABA significantly increased the percentage of starch and this percentage was decresed by increasing the ABA concentration . The liquid growing media was significantly superior in the quantitative and qualitative microtubers characters as compared with semi-solid grown media especially when 0.5 mg.l-1 ABA was used. The Revira cultivar was superior then Desiree in this studied characters except the percentage of starch which was not influenced by the cultivar or the physical status of the growing. The percentage of starch was increased in Desiree cultivar when 0.25 mg.l-1 ABA was added.